Studies on planar helical slow-wave structures for traveling-wave tube applications - Chua, Cier Siang (2012)
This thesis presents extensive studies on a new planar helix slow-wave structure (SWS) which consists of a planar helix with straight-edge connections (PH-SEC). The PH-SEC has been studied in the context of traveling-wave tube (TWT) applications. Unlike the conventional circular helix, the PH-SEC can be fabricated easily using printed circuit techniques or microfabrication techniques. In addition, by changing the aspect ratio, the PH-SEC can become suitable for interaction with a sheet electron beam which can offer many advantages for high frequency TWTs. To avoid oscillations at high power levels, the PH-SEC has also been modified into a rectangular ring-bar slow-wave structure with straight-edge connections (RRB-SEC); this modification is similar to that of the circular helix into the circular ring-bar SWS. For the PH-SEC, dispersion characteristics for several practical modifications to the basic structure have been examined. These modifications comprise a vacuum tunnel, metal shield and multilayer dielectric substrates. A modified effective dielectric constant (MEDC) method has been proposed to obtain the dispersion characteristics for the different possible configurations. Further, coupling impedance for the different configurations has been calculated using the corresponding two-dimensional approximations. Effects of variations in the aspect ratio, metal shield distance and dielectric constant of the substrates on the phase velocity and the coupling impedance have been studied. The PH-SEC structure incorporating coplanar waveguide (CPW) feed has been designed and fabricated for printed circuit fabrication and microfabrication. Effects of dimensional parameters have been studied. Several PH-SECs with band edge frequency less than 10 GHz have been fabricated using printed circuit techniques. The measured results for these structures validate the analytical results obtained using the MEDC method. A microfabrication process, involving several UV-LIGA steps, has been proposed and demonstrated to produce high-aspect-ratio PH-SEC structures at W-band (75 - 110 GHz). On-wafer measurements have been carried out on a number of microfabricated SWSs. The cold-test parameters (dispersion characteristics and coupling impedance) of the SWSs have also been obtained using simulations, and the effects of fabrication, such as surface roughness, have been accounted for by estimating effective conductivity of different parts of the microfabricated structures. It is shown that, compared to the PH-SEC, its modification, the RRB-SEC enhances the coupling impedance for the fundamental forward-wave while reducing the coupling impedance for the backward-wave. Detailed results for the phase velocity and the coupling impedance of the RRB-SEC have been presented to show the effects of structure dimensions. The RRB-SEC incorporating the CPW feed has also been designed and fabricated for W-band using the microfabrication process developed for the PH-SEC. A low power square aspect ratio PH-SEC incorporating a sever has been simulated with a circular cross-section electron beam at W-band using 3D CST Particle Studio. A simplified coupler, similar to the CPW, has been used in the Particle-In-Cell (PIC) solver. The linear and non-linear amplification of the input signal has been examined. The input and output couplers based on W-band (WR-10) rectangular waveguide have been designed for high power application. It is shown that the structure with the rectangular waveguide couplers leads to a ‘cleaner’ output compared to that with the CPW feed. A square aspect ratio RRB-SEC has also been designed with rectangular waveguide couplers. The studies reported in this thesis have potential applications in printed-circuit TWTs at low frequencies (<18GHz) and microfabricated TWTs at millimeter wave frequencies (30 - 300 GHz). The proposed microfabrication process can also be scaled to fabricate planar helical SWSs at terahertz frequencies (0.3 - 3 THz).